On rhetorical appeals: Emotionalization and politicization of Russia’s Covid-19 vaccine ‘Sputnik V’ in the American and Russian news discourse - Ekaterina Veselinovna Teneva; Ilya Bykov (Indonesian Journal of Applied Linguistics, 2023)
The relations between language and politics in Covid-19 coverage have become significant issues following the rise of Chinese Covid-19 cases in 2022. The study aims to investigate specific rhetorical appeals and language means that were used by journalists to manipulate public opinion and propagate certain ideology in the American and Russian online news discourse. The study employed a mixture of quantitative and qualitative research techniques. It used computer-assisted content analysis, rhetorical analysis, and van Dijk’s sociocognitive approach to CDA to identify and describe biased representations of Russia’s Covid-19 vaccine ‘Sputnik V’ in 307 Internet news text. The content analysis revealed frequent mentions of politicians and political institutions in the American and Russian coverage of ‘Sputnik V’. The rhetorical and discourse analyses expose similarities in the use of rhetorical appeals and language means. The study concludes that the coverage of ‘Sputnik V’ was highly emotionalized and politicized both in American and Russian media. The journalists utilized the ideologically loaded language and rhetorical appeals to disguise their biased opinions and create a distorted image of ‘Sputnik V’ in the online news coverage. The study also provides implications for the development of ESL and EFL courses to enhance students’ reading comprehension skills.